Increasing Mathematics Learning Outcomes Of Class IV Students Through Project Based Learning Models - Hartanti, Dwi Sugi (Universitas Sebelas Maret, 2022)
The purpose of this study was to improve the learning outcomes of fourth grade students at SD Negeri 01 Tohudan. The research conducted aims to improve student learning outcomes by using a Project Based Learning Model. The form of this research is classroom action research using a cycle model. Each cycle consists of 4 stages, namely planning, implementation, action, observation, and reflection. As the research object were the fourth grade students of SDN 01 Tohudan, totaling 26 children. Researchers in selecting objects not individually, but classically. Data collection is done by observing, testing, and documents. From the results of this study revealed the problem of students' low understanding of the material Changing Ordinary Fractions to Mixed Fractions so that the results of learning this material many students get scores below the Minimum Completeness Criteria (KKM), namely 70 in pre-cycle learning. Then the researcher made improvements to learning mathematics through two cycles. Each cycle consists of planning, implementing, observing, and reflecting. In Cycle I students obtained an average of 71.92 with 73.08% completeness and Cycle II obtained an average of 82.69 with 100% completeness. The results of the research using the Project Based Learning Model. Students' understanding of the material of Changing Ordinary Fractions into Mixed Fractions in class IV SD Negeri 01 Tohudan can improve student achievement in learning mathematics